1995
DOI: 10.1111/j.1600-0714.1995.tb01134.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and histopathological study of radicular cysts associated with primary molars

Abstract: Radicular cysts originating from primary teeth are considered rare. The study analyzed 49 primary molars with radiolucent lesions ranging from 4-15 mm in diameter. 73.5% of the lesions were diagnosed as radicular cysts, and 26.5% as granulomas. The lesions were more frequent in the mandible. All lesions were associated with severely decayed teeth and only 4 had previous pulp therapy. The present study and the survey of the literature suggest that radicular cysts associated with primary teeth are not rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
28

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 5 publications
(7 reference statements)
0
66
0
28
Order By: Relevance
“…Despite the high incidence of early childhood caries, leading to gross destruction of maxillary anterior teeth and pulpal death, the incidence of radicular cysts in such situations is significantly less. In contrast to this, few authors have reported radicular cyst in deciduous anterior teeth following traumatic injury [14,15]. Whereas many authors [16,17,18] have reported dentigerous cyst as a common sequelae following trauma to the primary predecessor, radicular cysts are comparatively rare.…”
Section: Discussionmentioning
confidence: 78%
“…Despite the high incidence of early childhood caries, leading to gross destruction of maxillary anterior teeth and pulpal death, the incidence of radicular cysts in such situations is significantly less. In contrast to this, few authors have reported radicular cyst in deciduous anterior teeth following traumatic injury [14,15]. Whereas many authors [16,17,18] have reported dentigerous cyst as a common sequelae following trauma to the primary predecessor, radicular cysts are comparatively rare.…”
Section: Discussionmentioning
confidence: 78%
“…O cisto radicular é um cisto odontogênico inflamatório decorrente de lesões pulpares causadas por cárie ou traumas 7 . De acordo com a atual classificação internacional da Organização Mundial de Saúde (OMS) 11 , os cistos odontogênicos são classificados em dois grupos principais, que refletem sua patogênese.…”
Section: Revisão Da Literaturaunclassified
“…Dentre as lesões císticas nos maxilares, são os mais comuns envolvendo de 52% a 68% de todos os cistos da cavidade bucal. Ocorrem com maior frequência em homens, entre 20 a 40 anos de idade 5 , e são mais prevalentes nos brancos do que em negros 6,7 . A maior parte dos cistos radiculares não apresenta sintomatologia, mas pode haver dor ou sensibilidade se ocorrer exacerbação inflamatória aguda.…”
Section: Introductionunclassified
“…According to a study by Mass, et al in 1995, the mean age of all the cases studied was 7.7-years-old, with an almost equal distribution between genders [2]. In relation to the location in the arcades, the mandibular primary teeth are affected more frequently than the maxillary teeth [3].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology is related to pulp injuries or pulp necrosis caused by deep dental caries or dental trauma [2]. According to Bernardi, et al [5], the mechanism to develop radicular cyst includes pulp necrosis, colonization and proliferation of microorganisms within the root canal system, release of bacteria toxins and inflammatory mediators into the periapical region and a combination of factors involving epithelial-stromal interaction.…”
mentioning
confidence: 99%